Development and evaluation of power operated weeder in rice - Guru, P K; Patel, S P; Nayak, A K; Kumar, Anjani; Lal, B; Gautam, P (ORYZA-An International Journal of Rice, 2018)
A power operated single row dry land weeder for inter row weeding was developed and evaluated in rice crop and compared with traditional methods of manual weeding. The power weeder consisted of engine, blades assembly and transmission system. Vertical J shape blades were developed and mounted on a circular rotating element on its horizontal side; the motion was transferred to blades units by amended transmission system. The rotating blades cut the weeds and also give forward motion to the machine. Three different row to row spacing 20 cm, 25 cm and 30 cm and four different type of blade having width 12 cm, 14 cm, 16 cm and 18 cm has been used in the study. The effect of blade width on forward speeds, depth of operation, field capacity, plant damage,and weeding efficiency, were studied. Cost of operation and energy required per unit area were studied in comparison to the traditional methods. It was found that plant damage and weeding efficiency increased with increase of blade width. For row to row spacing of 20 cm, 25 cm and 30 cm, blade width of 14 cm, 16 cm and 18 cm, respectively, was recommended because of less plant damage and high weeding efficiency. The developed power weeder helps in reduction of drudgery involved in weeding operation and it also reduces the costinvolved in the operation.